IMPROVING THE LISTENING COMPREHENSION OF THE FIRST YEAR STUDENTS OF A STATE SENIOR HIGH SCHOOL IN ENREKANG, INDONESIA - Ita Sarmita Samad (Universitas Muhammadiyah Enrekang, 2018)
This study aims at finding out whether or not the implementation of jigsaw listening improves the Listening comprehension of the first year students of a state senior high school in Enrekang. This study employs a quasi experimental method. The population of this study is the first year students of a state senior high school in Enrekang in the academic year 2012/2013. It uses random sampling, taking two classes totalling 52 students. It involves two groups, namely experimental class and control class. The students’ pre-test and post-test shows that there is significance different between experimental and control group. The result of the gained of mean score shows the difference between those groups. The difference of the mean score of pre-test and post-test of experimental group is 16.62 while control group is 0.73. It means that . The students of experimental group get better improvement than the students’ of control group. Thus, it can be concluded that the hypothesis is tenable. Besides, the t-test value of gained score (2.65) is higher than t-table (2.021). Thus, it can be concluded that the jigsaw listening improves the students’ listening comprehension.